2021
DOI: 10.3389/fpsyg.2021.633037
|View full text |Cite
|
Sign up to set email alerts
|

Visual Sensory Experiences From the Viewpoint of Autistic Adults

Abstract: Although previous research has investigated altered sensory reactivity in autistic individuals, there has been no specific focus on visual sensory experiences, particularly in adults. Using qualitative methods, this study aimed to characterize autistic visual sensory symptoms, contextualize their impact and document any associated coping strategies. A total of 18 autistic adults took part in four focus groups which involved questions around visual experiences, the impact of these on daily life, and strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 89 publications
(135 reference statements)
0
23
1
Order By: Relevance
“…18 Furthermore, qualitative research has highlighted that autistic adults can be overwhelmed by and avoid certain public places, such as large shops, hospitals, cinemas, pubs, and libraries due to the sensory environment. 19,20 It is possible that adapting these environments will help autistic individuals to participate in public spaces. For example, research has shown that adapting the sensory environment in classrooms improved children's mood and performance.…”
Section: Introductionmentioning
confidence: 99%
“…18 Furthermore, qualitative research has highlighted that autistic adults can be overwhelmed by and avoid certain public places, such as large shops, hospitals, cinemas, pubs, and libraries due to the sensory environment. 19,20 It is possible that adapting these environments will help autistic individuals to participate in public spaces. For example, research has shown that adapting the sensory environment in classrooms improved children's mood and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Note that sensory behaviors reported in ASD are relatively heterogenous as there are inter‐individual differences in the intensity and evolution of the sensory features (Dwyer et al, 2020). Qualitative approaches with focus groups can also assess self‐reported sensitivity/responsivity in ASD and revealed a range of visual hypersensitivities/over‐responsivities in autistic adults, which negatively impact their daily lives (Parmar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining questions, (Q1) “Does anybody feel they experience any visual issues or unusual visual symptoms?”; (Q2) “Do you feel you can do anything to improve these symptoms” and (Q3) “How do your visual issues impact your daily routine?”, are discussed in another article about autistic visual sensory experiences 34 …”
Section: Study 1: Methodsmentioning
confidence: 99%